Carnauba bagana substrate and application of humic substances on the production of yellow passion fruit seedlings - da Silva, João Pedro; da Silva-Matos, Raissa Rachel Salustriano; de Paulo Barbosa, Larissa Macelle; Costa, Romário Martins; Matos, Sâmia Dos Santos; Araújo, Misael Batista Farias [UNESP] (FapUNIFESP (SciELO), 2022)
Owing to the high prices of agricultural inputs, it is necessary to seek alternatives that minimize costs during the seedling production stage, such as the use of agro-industrial residues to formulate substrates and the application of humic substances to increase the availability of nutrients. This study aimed to evaluate the production of yellow passion fruit seedlings in substrates based on carnauba bagana under increasing doses of humic substances. The design was completely randomized, in a 3 x 4 factorial scheme, referring to three substrates formulated with carnauba bagana (0, 50 and 100 %) plus soil and four doses of humic substances (0, 12.5, 25 and 50 g L-1). The use of carnauba bagana in the substrate increased the leaf area, plant height, stem diameter, root length, root volume, shoot and root dry mass, and improved the seedlings quality. The application of humic substances to the substrate did not stimulate the seedlings development.
Substrato de bagana de carnaúba e aplicação de substâncias húmicas na produção de mudas de maracujazeiro amarelo
Keywords: alternative substrates; Copernicia prunifera; Passiflora edulis